The influence factors of tour guides' professional identity and professional decision before and after the COVID-19 pandemic - Wenwen Hu; Qing Yuan; Yaxi Wang; Nan Chen (Heliyon, 2024)
The COVID-19 pandemic has significantly impacted the tourism sector, particularly tour guides (TGs), affecting their professional identity (TGPI) and intentions to return to work. As China strives to revive its tourism industry, it is crucial to understand the current state of TGPI, its evolution, influencing factors, and its impact on TGs' return intentions. This study employed a quantitative approach, using comparative analysis and binary logistic regression, to investigate these issues among frontline TGs in China, pre- and post-pandemic. Cross-sectional surveys were conducted with 422 participants in 2019 and 398 in 2022, yielding 370 and 342 valid responses, respectively. The questionnaire utilized a five-point Likert scale. Findings reveal that (1) The overall TGPI level in 2022 post-pandemic is medium (3.93), showing a significant decrease from the pre-pandemic level in 2019 (4.15). (2) Influencing factors of TGPI are predominantly material, reflected in social insurance and income changes pre- and post-pandemic. (3) This study presents a novel definition and scale of TGPI, encompassing tour guides' professional value identity (TGPVI), emotion identity (TGPEI), relationship identity (TGPRI), and behavior tendency (TGPBT). (4) The two dimensions of the TGPI, TGPVI and TGPRI, income and education level, significantly influence TGs' return intentions. The study provides valuable academic and practical insights into TGPI and offers significant implications for enhancing TGs' return intentions and policymaking for post-pandemic tourism industry development.